2014
DOI: 10.1002/uog.13506
|View full text |Cite
|
Sign up to set email alerts
|

OC07.04: Adjusted cervical length for gestational age as predictor of urgent delivery in pregnancies complicated by placenta previa

Abstract: Oral communication abstracts cases respectively. The cervix was measured using three techniques between the external os (EO) and the internal cervical os (IO) (single straight line, two straight lines, tracing), and the same three techniques between the external os and the lower pole of the egg (LPE). All measurements were repeated to assess the intra and inter operator variability. The value of measurements to predict PTB was compared based on ROC curves. Results: Mean cervical length examined by the single-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Another study also argued that a single measurement of CL is not sufficient to predict the outcome [ 13 ]. A recent study showed that CL in women with placenta previa is a useful predictor of emergency CS due to bleeding or labor, and improved its utility by using CL Z -scores adjusted for gestational age [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study also argued that a single measurement of CL is not sufficient to predict the outcome [ 13 ]. A recent study showed that CL in women with placenta previa is a useful predictor of emergency CS due to bleeding or labor, and improved its utility by using CL Z -scores adjusted for gestational age [ 17 ].…”
Section: Discussionmentioning
confidence: 99%